Características socioeconómicas que influyen en la probabilidad de acceso a internet en los hogares de la provincia de Maynas 2022 - Pinedo Chuquipiondo, Leticia Lorena (2025)
The internet connection has acquired an essential place in daily life, playing a fundamental role in communication, education and employment, among other aspects. In addition, internet access promotes social inclusion and contributes to economic development by providing new opportunities for innovation and collaboration at a global level. The present research provides an clarifying vision on the influence of various socioeconomic characteristics on the probability of internet access in homes in Maynas during the year 2022. With a quantitative, correlational-level approach and a non-experimental design with cross-sectional data, the research comprehensively addresses the relationship between the selected variables and the probability of internet access. The results obtained through the logit model reveal that the probability of internet access in homes in Maynas is 51.42%. This percentage shows a positive connection with factors such as the presence of adequate infrastructure, higher monthly spending per household member, participation in formal jobs, and improvement in the educational level of household members.